2023
DOI: 10.1111/1750-3841.16706
|View full text |Cite
|
Sign up to set email alerts
|

Bergamot juice powder with high bioactive properties: Spray‐drying for the preservation of antioxidant activity and ultrasound‐assisted extraction for enhanced phenolic compound extraction

Abstract: The spray‐drying process yielded functional bergamot juice powder with high antioxidant activity, phenolic content, and vitamin C content. Optimal drying conditions were determined as 10% maltodextrin concentration, 146.02°C inlet temperature, and 39.99% pump rate, preserving powder's bioactive properties. Under these drying conditions, bergamot juice powder exhibited an antioxidant activity of 62.2% DPPH scavenging activity, a total phenolic content of 3862.1 ppm, and a vitamin C content of 1385.9 ppm. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Continuing our previous work [ 8 ], a 50% acetone (ACTN) solvent concentration produced a phenolic-rich bergamot juice powder extract. Initially, 1 g of powder was combined with ACTN to match the juice’s initial water-soluble solids content (7.93%).…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…Continuing our previous work [ 8 ], a 50% acetone (ACTN) solvent concentration produced a phenolic-rich bergamot juice powder extract. Initially, 1 g of powder was combined with ACTN to match the juice’s initial water-soluble solids content (7.93%).…”
Section: Methodsmentioning
confidence: 65%
“…The edible coating formulation used low-molecular-weight chitosan (EC 223-311-2, CAS 9012-76-4, Sigma-Aldrich, Co., Saint Louis, MO, USA). To enhance the coating formulation, readily available bergamot ( Citrus bergamia Risso et Poiteau) fruit juice powder was previously produced in another study [ 8 ]. Analytical and chromatographically pure chemicals were sourced from reputable suppliers, including Sigma-Aldrich, Merck, Carlo Erba, Isolab, Riedel-de Haën, and Oxoid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bergamot fruit ( C. bergamia Risso et Poiteau) used in this study was sourced from Tekirova‐Antalya, Turkey, in February 2022. These bergamots, particularly their peels, were the same as those characterized in our prior research (Demircan et al., 2023). The trees, which belonged to the Italian‐originated Castagnaro variety, were cultivated by experienced farmers in moderately sunny and lightly shaded areas.…”
Section: Methodsmentioning
confidence: 99%
“…Sicari et al (2016) found that the geographical area of production influenced color (L* 1.83-7.60; a* 0.05-0.29; b* 0.60-4.82); pH (2.54-2.84); acidity (11.38-14.83 g/L); formol index (2.53-3.66); ascorbic acid (89.40-285.35 mg/100 mL); flavonoid content (51.11-148.15 mg/100 mL); and polyphenol content (180.53-233.36 mg/100 mL). Additionally, bergamot exhibits a total water-soluble solid of 7.93%, a pH of 2.77, an acidity of 2.56%, a vitamin C content of 20,335 mg/100 g, antioxidant activity of 79.23%, a total phenolic content of 53,745 mg/100 g, and total flavonoids of 8450 mg/100 g (Demircan et al, 2023;Giuffrè, 2019).…”
Section: Introductionmentioning
confidence: 99%